Evaluating Distal and Proximal Explanations for Withdrawal: A Rejoinder to Varnum and Kwon’s “The Ecology of Withdrawal” - Norasakkunkit, Vinai; Uchida, Yukiko; Takemura, Kosuke (Frontiers in Psychology, 2017)
In their 2016 commentary on our theorizing about how youth withdrawal from economic and social participation in Japanese society (i.e., NEET and Hikikomori phenomena) stems from generational inequality of economic opportunities, Varnum and Kwon correctly point out that our explanation for withdrawal is yet untested. They then offered an alternative, evolutionary psychological explanation for withdrawal in which they claim that in resource-rich ecologies like Japan, the option to withdraw from participating in society is a possible life strategy, a strategy that would be much more costly in resource-poor ecologies. While we agree with this premise, we argue that this distal explanatory framework, at least in its current form, has limits in reconciling some of the more recent cross-cultural observations, as well as well-established sociological claims about the causes of withdrawal. Thus we argue that much work remains in refining and expanding the explanatory power of more distal explanations on the issue of withdrawal. Until then, the more proximal and culture-specific explanations are probably the useful and meaningful explanations for the withdrawal phenomenon.